Pengaruh Interaksi Pelanggan Di Instagram Dalam Meningkatkan Brand Awareness Terhadap Loyalitas Konsumen Di Poljam Mart - Melia N; Dedi Handoko Handoko; Pramesti Nurul Adinda Adinda (Journal of Applied Accounting And Business, 2026)
To study aims to analyze the influence of Customer Interaction on Instagram and Brand Awareness on Customer Loyalty at Poljam Mart. In the era of digital transformation, two-way communication strategies and strengthening brand identity are essential for retail business units to retain customers. The research method employed is quantitative, utilizing multiple linear regression analysis. Data were collected through questionnaires distributed to respondents who are customers of Poljam Mart and followers of their official Instagram account. The results indicate that, partially, Customer Interaction has a positive and significant effect on Customer Loyalty (tcount 2.957; Sig 0.004). Similarly, Brand Awareness exerts a dominant positive and significant influence on Customer Loyalty (tcount 6.377; Sig. 0.000). Simultaneously, both independent variables significantly affect Customer Loyalty (Fcount 89.411) with a contribution of 67.3%, as indicated by the coefficient of determination (R2) value of 0.673. These findings suggest that the combination of active social media engagement and strong brand recognition is an effective strategy for increasing customer retention at Poljam Mart. Keywords: Customer Interaction, Brand Awareness, Customer Loyalty, Instagram, Poljam Mart.